2018
DOI: 10.1016/j.jecp.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying attentional effects on the fidelity and biases of visual working memory in young children

Abstract: Attentional control enables us to direct our limited resources to accomplish goals. The ability to flexibly allocate resources helps to prioritize information and inhibit irrelevant/distracting information. We examined developmental changes in visual working memory (VWM) fidelity in 4- to 7-year-old children and the effects that a distracting non-target object can exert in biasing their memory representations. First, we showed that VWM fidelity improves from early childhood to adulthood. Second, we found evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 83 publications
(117 reference statements)
3
13
0
Order By: Relevance
“…Recently, Guillory et al. (2018) tested 4–7‐year‐olds’ precision in reporting the orientation of target stimuli in WM when targets were followed or preceded by an orientation distractor and when their attention was cued in preparation for encoding or during maintenance. Overall precision of recall was poorer in children compared to adults.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Guillory et al. (2018) tested 4–7‐year‐olds’ precision in reporting the orientation of target stimuli in WM when targets were followed or preceded by an orientation distractor and when their attention was cued in preparation for encoding or during maintenance. Overall precision of recall was poorer in children compared to adults.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of research examining the development of the ability to store information about objects in working memory. This work has shown that the number of object representations that can be stored in working memory increases throughout infancy and childhood (Cowan et al, 2011; Káldy & Leslie, 2005; Kibbe, 2015; Kibbe & Leslie, 2011, 2013; Pailian et al, 2016; Ross-Sheehy et al, 2003; Simmering, 2012), as does the fidelity and precision of those stored representations (Applin & Kibbe, 2020; Burnett Heyes et al, 2012; Cheng et al, 2020; Guillory et al, 2018). The ability to maintain bindings between objects’ surface features (e.g., color, shape, texture) and their locations in space is extremely limited in early development, increasing from about one feature-location binding at 6 months (Káldy & Leslie, 2005; Kibbe & Leslie, 2011), to around two feature-location bindings in toddlerhood (Cheng et al, 2019a; Kibbe & Applin, 2022; Kibbe & Leslie, 2013), to around four feature-location bindings at 5–6 years of age (Applin & Kibbe, 2020).…”
mentioning
confidence: 99%
“…However, we did not have specific predictions about the impact of set size on children’s performance. Previous work found that the precision of visual working memory increases with development (Guillory, Gliga, & Kaldy, 2018; Sarigiannidis, Crickmore, & Astle, 2016), as does the ability to bind feature and location information in visual working memory (Kibbe & Leslie, 2013; Simmering & Wood, 2017). Children are estimated to be able to hold anywhere from two to four single-feature items or two multifeature items in visual working memory during a change-detection task by age 5–6 (Pailian et al, 2016; Riggs et al, 2006; Simmering, 2012; Simmering & Wood, 2017) and around three multifeature objects by age 7 (Burnett Heyes, Zokaei, van der Staaij, Bays, & Husain, 2012; Riggs et al, 2011).…”
mentioning
confidence: 99%